491 EVALUATION OF AIRWAY EDEMA FROM SMOKE INHALATION USING OPTICAL COHERENCE TOMOGRAPHY. (1st January 2006) - Tseng, L.; Mukai, D.; Guo, S.; Kreuter, K.; Brenner, E.; Chen, Z.; Brenner, M.
Abstract : Background: Optical coherence tomography (OCT) is a non-invasive, high-resolution imaging technology that is capable of delivering real-time, near histologic level images of tissues. Acute smoke inhalation causes airway edema, which leads to major morbidity and mortality, but the ability to assess airway injury in a clinical setting is limited. The purpose of this study is to assess the ability of OCT to detect and monitor progression of inhalation airway injury with minimally invasive techniques. Methods: A ventilated New Zealand White rabbit smoke inhalation injury model using fumes from burnt unbleached cotton was employed to simulate acute smoke inhalation injury. A 1 mm diameter flexible fiberoptic OCT probe was introduced into the distal trachea to image airway mucosa and submucosa. Progression of injury edema was measured over 6 hours with OCT imaging using a prototype superluminescent diode OCT system we constructed in our laboratory. OCT tracheal images from the smoke inhalation injury animals were compared to control rabbit tracheas for quantitative tracheal mucosal thicknesses measurements. Results: Results revealed significant airway mucosal thickening in the experimental group consistent with tracheal edema, which occurs as early as 30 minutes after smoke inhalation. Conclusion: OCT is a valuable imaging modality capable of evaluating superficial airway pathology with high resolution in vivo after acute inhalation injury.